PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL TEACHING LEARNING (CTL) PADA PELAJARAN TEMATIK DI KELAS III SDS JAKARTA ISLAMIC SCHOOL - MUNANDAR , ASEP RISDIAN (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2024)
This study aims to improve students' learning outcomes on the theme of "Recognizing Objects Around Me" at SDS Jakarta Islamic School, East Jakarta. The subjects of this study were 3rd-grade students at SDS Jakarta Islamic School, East Jakarta, with a total of 15 students. The improvement of students' learning outcomes was carried out through three learning cycles, namely the pre-cycle on Wednesday, September 5, 2018, cycle 1 on Thursday, September 13, 2018, and cycle 2 on Thursday, September 19, 2018, using classroom action research. Based on data analysis and statistics from the results and discussion of this study, there was a significant increase in the average value in each cycle. This was indicated by the average value obtained in the pre-cycle of 61.5, which increased in cycle 1 to an average value of 72 and increased in cycle 2 to an average value of 80. Thus, it can be concluded that through the application of the contextual teaching and learning model, students' learning outcomes in the class of "Recognizing Objects Around Me" at SDS Jakarta Islamic School, East Jakarta, can be improved. ABSTRAKPenelitian ini bertujuan untuk meningkatkan hasil belajar pada tema Mengenal Benda di Sekitarku di SDS Jakarta Islamic School Jakarta Timur. Subyek dalam penelitian ini adalah siswa kelas III SD di SDS Jakarta Islamic School Jakarta Timur dengan subjek sebanyak 15 siswa. Perbaikan hasil belajar siswa dilakukan dengan 3 siklus pembelajaran yaitu pada saat Prasiklus Rabu 5 september 2018, siklus 1 Kamis 13 September 2018 dan siklus 2 Kamis 19 September 2018 dengan menggunakan penelitian tindakan kelas. Berdasarkan data analisis dan statistik dari hasil dan pembahasan penelitian ini terjadi peningkatan nilai rata-rata yang cukup signifikan pada setiap siklus, hal ini ditunjukkan dengan perolehan nilai rata-rata pra siklus 61,5 meningkat pada siklus 1 dengan nilai rata-rata 72 dan meningkat pada siklus2 dengan nilai rata-rata 80. Jadi dapat disimpulkan bahwa melalui penerapan model pembelajaran kontekstual dapat meningkatkan hasil belajar siswa kelas Mengenal Benda di Sekitarku di SDS Jakarta Islamic School Jakarta Timur.